2019
DOI: 10.1111/pops.12582
|View full text |Cite
|
Sign up to set email alerts
|

Voters’ Partisan Responses to Politicians’ Immoral Behavior

Abstract: Politicians’ moral behaviors affect how voters evaluate them. But existing empirical research on the effects of politicians’ violations of moral standards pays little attention to the heterogeneous moral foundations of voters in assessing responses to violations. It also pays little attention to the ways partisan preferences shape responses. We examine voters’ heterogeneous evaluative and emotional responses to presumably immoral behaviors by politicians. We make use of moral foundation theory’s argument that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…Furthermore, we found that moral foundations did not predict the longitudinal change in intergroup attitudes. These results support former experimental (Ciuk, 2018;Eriksson et al, 2019;Walter & Redlawsk, 2019) and longitudinal studies (Hatemi et al, 2019;Smith et al, 2017) which concluded that moral values (measured as moral foundations) are not necessarily bases of our social beliefs, but are consequences of them since people tend to reset their moral priorities to get them in line with their current motivated social beliefs. Besides supporting this idea, our study took one step further and demonstrated in a real-life political context that people rely on the available information provided by political communication when doing this moral reset.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, we found that moral foundations did not predict the longitudinal change in intergroup attitudes. These results support former experimental (Ciuk, 2018;Eriksson et al, 2019;Walter & Redlawsk, 2019) and longitudinal studies (Hatemi et al, 2019;Smith et al, 2017) which concluded that moral values (measured as moral foundations) are not necessarily bases of our social beliefs, but are consequences of them since people tend to reset their moral priorities to get them in line with their current motivated social beliefs. Besides supporting this idea, our study took one step further and demonstrated in a real-life political context that people rely on the available information provided by political communication when doing this moral reset.…”
Section: Discussionsupporting
confidence: 88%
“…But as Walter and Redlawsk (2019) find in examining valence emotion, the potential impact of immoral behavior by politicians is conditioned by partisanship. 2 They view partisanship as a group identity (Mason, 2018), such that when an in-party politician violates moral imperatives, co-partisans do not have the negative emotional response one might anticipate.…”
mentioning
confidence: 93%
“…However, it may be that this finding is an artifact of their analytical approach. While Haidt (2003) defines a set of discrete moral emotions, Walter and Redlawsk (2019) examine only valence emotion-obscuring the effects of specific emotional responses. In this paper we extend this by considering a set of discrete moral emotions and examining how these moral emotional responses depend on voters' own moral principles and partisan group identity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All else equal, voters favor politicians who are free of scandals such as tax evasion, marital infidelity, or corruption (Basinger, 2013; Carlson et al, 2000; Doherty et al, 2011; Funk 1996; Sigal et al, 1988). On the other hand, voters’ evaluations of politicians accused of unethical behavior are shaped by their preconceived perceptions (Fischle, 2000) and partisanship can be a stronger driver of voters’ responses to immoral behavior than their moral foundations (Walter and Redlawsk, 2019).…”
Section: Partisan Motivated Reasoning and Reactions To Scandalmentioning
confidence: 99%